PENERAPAN STRATEGI DIFERENSIASI OLEH GURU UNTUK MEMENUHI KEBUTUHAN BELAJAR SISWA DI SEKOLAH DASAR - Nihaya; Citra; Shenty Pertywy; Nurkholis (PT. Hasba Edukasi Mandiri, 2025)
The role of teachers in implementing learning strategies is crucial to meeting the diverse learning needs of students. Since each student differs in terms of character, interests, readiness, and learning styles, teachers are required to create flexible and adaptive learning experiences. The aim of this study is to describe various strategies employed by teachers to adjust learning processes to meet students' individual needs. This research uses a qualitative descriptive approach, combining literature studies and direct field observations to obtain in-depth information. The findings show that strategies such as differentiated instruction, the use of diverse learning media, and the application of a humanistic approach are effective methods for creating an inclusive and meaningful learning process. These approaches can increase student engagement, stimulate creativity, and help achieve learning objectives optimally. Thus, the teacher's ability to select and apply the right strategies becomes a key factor in supporting students' academic development and character formation.